THE PRESERVATION OF RUSSIAN FOLK CRAFTS AS ONE OF THE FACTORS IN THE DEVELOPMENT OF ART EDUCATION (Irkutsk region) - Lovtsova, I.V. (Tambov University Review. Series: Humanities, 2016)
The problem of national culture preservation by making the transfer of experience of folk craftsmen an integral part of the content of art education is discussed. The importance of such education and its functions in conservation, reproduction and development of national culture is studied. The idea is considered that the possibilities inherent to folk art enrich the content of art education and thus require to be preserved and developed. To illustrate the thesis, examples of positive experience of preservation and development of folk crafts from the practice of the Irkutsk region are provided. The preservation and development of Russian folk crafts require close attention and constant systematic support, also as a part of artistic education in Russia. A theoretical basis and a roadmap for the development of art education in the field of decorative-applied art and folk crafts is provided. These issues in connection with the basic art education are analyzed. Further development of traditions of Russian folk arts, crafts and trades at colleges and universities is also studied.